Resistance in political theatre of Saadallah Wannus - AlAyyat, Iman Ahmed (AUC Knowledge Fountain, 2016)
Sa’d Allah Wannūs (1941-1997) was a renowned Syrian playwright whose plays aimed at stimulating audience’s reactions against the impacts of the political situation after the setback of 1967. Wannūs first highlights the complex interrelationship between the rise of power structures and hegemonic rule colored by the leaders’ aspirations. Such collision with inexorable mapping of reality incites the audience to incarnate an inspiring future that is not influenced by the past or co-opted with the complex interrelated power structures. Wannūs portrays a world that the French philosophers Gilles Deleuze (1925-1995) and Felix Guattari (1930-1992) theorize as the “rhizome” in which hegemonic societies are established in horizontal de-territorialized structures rather than vertically rooted. Because this structure is mapped rather than traced, the Australian critic Bill Ashcroft suggests that this resisting structure is an opportunity for transformation and way out from the historical hegemony. Deleuze describes this transformation as exemplified in literature by transforming the hegemonic cultures not through “logic of predication of truth”; that is, the author does not embellish the future or propose predictions, but through refracting from the tracings and then mapping the “logic of sense” in reaching the “becoming” assemblage; that is the author highlights that change is required but he does not spell out this change; he urges the audience to take the lead and role to remap the future. Wannūs also adapts the Brechtian techniques of estrangement in the Arabic theatre in order to involve audience in the status que and awaken their responsibility. Wannūs uses Brechtian dramatic techniques in certain extent. However, he adapts the Arabic environment in order to ensure the involvement of laymen. This thesis selects works by the Syrian playwright Wannūs that were published in 1968 through 1996, as they are illuminated by the theoretical framework of Brecht, Deleuze and Guattari, and the critical writing of Wannūs, in political theatre.